Employment Agreement in the Perspective of Business Civil Law - Masitah Pohan (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Civil law was created as an effort to create a law that should exist to assist business or trade processes and activities, through this law, of course, business activities will also not violate applicable laws. The reasons why this rule is needed by business people include making it clear which parties involved in a business will need something more official and no longer about promises or just good faith. The type of research used in this writing is library research. Library research means research that uses written documents as data, and the data sources used in this research include primary legal materials, secondary legal materials and tertiary materials. Primary legal materials are legal materials that bind or make people obey the law, including legal products that are the subject of study and legal products as a means of criticism. Secondary legal materials include explanations of primary legal materials in the form of expert doctrines found in books, journals, and on websites. According to Article 1601a of the Civil Code, what is meant by a work agreement is an agreement where one party, the worker, binds himself to work for another party, the employer, for a certain time, by receiving wages, based on Law No. 13 of 2003 concerning Employment is explained that, a work agreement is an agreement between a worker/labourer and an entrepreneur or employer that contains the terms of work, rights and obligations of the parties. Agreements in the management of a business have a very important role. In the business world, every agreement will be formally stated through an engagement, so that the agreement will have legal force and power that compels the parties to be obeyed and implemented